THE INFLUENCE OF ORGANIZATIONAL CULTURE AND WORK ABILITY ON EMPLOYEE PERFORMANCE WITH WORK DISCIPLINE AS AN INTERVENING VARIABLE AT THE NORTH SUMATRA PROVINCIAL YOUTH AND SPORTS OFFICE - Tengku Zuhry Al Hassany; Teguh Wahyono; Yohny Anwar (Yayasan Multidimensi Kreatif, 2025)
This study aims to analyze the influence of organizational culture and work ability on employee performance, as well as assess the role of work discipline as a mediating variable in the North Sumatra Provincial Youth and Sports Office. The results of the study show that organizational culture has a positive and significant influence on employee performance. Similarly, employability has a positive and significant influence on employee performance. In addition, organizational culture and work ability have also been proven to have a positive and significant effect on work discipline. Work discipline itself has a positive and significant effect on employee performance. Furthermore, work discipline plays a significant mediating variable in the relationship between organizational culture and employee performance. Work discipline also mediates the relationship between work ability and employee performance significantly. These findings indicate that improving organizational culture and work ability, through strengthening work discipline, can effectively improve employee performance. This research provides practical implications for human resource management, especially in designing sustainable employee performance improvement strategies.